Adaptive Back-stepping Stability Control Strategy for MMC Based on Legendre Polynomial - Lei XU; Xiangyang XIA; Huabing JING; Yixuan LIU; Yedan HE; Haigan YI (Zhongguo dianli)
In view of the poor stability control performance and frequent operation faults of the flexible HVDC transmission system due to the parameter changes of system dynamic model structure caused by serious signal interference or device temperature rise during the operation of the modular multilevel converter(MMC), an adaptive back-stepping stability control strategy is proposed based on Legendre polynomial. Firstly a dynamic model is established in a static a-b-c coordinate system, and the Legendre polynomial, which has advantages of simple structure and no modeling, is used to approximately compensate for the error value caused by the parameter changes in MMC, thus eliminating its effects on dynamic model. Then, the back-stepping control theory is used to select the state variables, construct the Lyapunov function, and obtain the control variables that meet the requirements of Lyapunov stability. Finally, simulation verification is carried out through PSCAD/EMTDC, which shows that the control strategy proposed in this paper has better control ability and robustness than the conventional PI control strategy.